Utility of Apical Lung Assessment on Computed Tomography Angiography as a COVID-19 Screen in Acute Stroke. Issue 12 (December 2020) - Esenwa, Charles; Lee, Ji-Ae; Nisar, Taha; Shmukler, Anna; Goldman, Inessa; Zampolin, Richard; Hsu, Kevin; Labovitz, Daniel; Altschul, David; Haramati, Linda B.
Abstract : Background and Purpose: Evaluation of the lung apices using computed tomography angiography of the head and neck during acute ischemic stroke (AIS) can provide the first objective opportunity to screen for coronavirus disease 2019 (COVID-19). Methods: We performed an analysis assessing the utility of apical lung exam on computed tomography angiography for COVID-19–specific lung findings in 57 patients presenting with AIS. We measured the diagnostic accuracy of apical lung assessment alone and in combination with patient-reported symptoms and incorporate both to propose a COVID-19 era AIS algorithm. Results: Apical lung assessment when used in isolation, yielded a sensitivity of 0.67, specificity of 0.93, positive predictive value of 0.19, negative predictive value of 0.99, and accuracy of 0.92 for the diagnosis of COVID-19, in patients presenting to the hospital for AIS. When combined with self-reported clinical symptoms of cough or shortness of breath, sensitivity of apical lung assessment improved to 0.83. Conclusions: Apical lung assessment on computed tomography angiography is an accurate screening tool for COVID-19 and can serve as part of a combined screening approach in AIS. Abstract : Supplemental Digital Content is available in the text.